2013
DOI: 10.1172/jci71714
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SOD1 reduces experimental non–small-cell lung cancer

Abstract: Approximately 85% of lung cancers are non-small-cell lung cancers (NSCLCs), which are often diagnosed at an advanced stage and associated with poor prognosis. Currently, there are very few therapies available for NSCLCs due to the recalcitrant nature of this cancer. Mutations that activate the small GTPase KRAS are found in 20% to 30% of NSCLCs. Here, we report that inhibition of superoxide dismutase 1 (SOD1) by the small molecule ATN-224 induced cell death in various NSCLC cells, including those harboring KRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 42 publications
10
159
0
1
Order By: Relevance
“…The finding that distant metastasis is limited by oxidative stress is not an artifact of xenotransplantation into immunocompromised mice as similar results were observed in immunocompetent mice with autochthanous melanomas: Treatment with NAC or vitamin E promoted distant metastasis without affecting the growth of subcutaneous tumors (Le Gal et al 2015). Consistent with this, cancer cells depend on NRF2 (Wang et al 2016), thioredoxinlike 2 (Qu et al 2011), superoxide dismutase (Kamarajugadda et al 2013;Glasauer et al 2014), and glutamate cysteine ligase (the rate-limiting step of glutathione synthesis) (Nguyen et al 2016) to survive during metastasis.…”
Section: Ros and Metastasismentioning
confidence: 64%
“…The finding that distant metastasis is limited by oxidative stress is not an artifact of xenotransplantation into immunocompromised mice as similar results were observed in immunocompetent mice with autochthanous melanomas: Treatment with NAC or vitamin E promoted distant metastasis without affecting the growth of subcutaneous tumors (Le Gal et al 2015). Consistent with this, cancer cells depend on NRF2 (Wang et al 2016), thioredoxinlike 2 (Qu et al 2011), superoxide dismutase (Kamarajugadda et al 2013;Glasauer et al 2014), and glutamate cysteine ligase (the rate-limiting step of glutathione synthesis) (Nguyen et al 2016) to survive during metastasis.…”
Section: Ros and Metastasismentioning
confidence: 64%
“…A number of observations potentially implicate SOD1 in tumorigenesis (114). For example, increased SOD1 expression was found in a panel of breast cancer cell lines (113); overexpression of SOD1 promotes growth of lung cancer cells (152); and inhibition of SOD1 induces cell death in the lung carcinoma cell line A549 (49). Mutation of the SOD1 succinylation site inhibited the growth of lung cancer cells (88), suggesting a role for SIRT5-mediated SOD1 desuccinylation and activation in promoting tumorigenesis.…”
Section: Metabolic Targets Of Sirt5mentioning
confidence: 99%
“…In fact, proteins such as cofilin (34), vimentin (115), and alpha-1-antitrypsin (116,117) were also shown to be more oxidized in the normal epithelium of the airways distant to the neoplasm in patients with LC (25), and their function was altered as a result of the oxidative posttranslational modifications, which may contribute to lung destruction and emphysema (116,117).…”
Section: Redox Balancementioning
confidence: 99%
“…The conclusions from these findings were that SOD2 may be a key survival mechanism for the cancer cells to proliferate in the tumors. In fact, another investigation (34) demonstrated that inhibition of SOD activity reduced tumor burden in mice and promoted cell death in several NSCLC lines of cells. Furthermore, SOD2 was also shown to favor cell migration and invasiveness of tumors in other investigations (117,118).…”
Section: Redox Balancementioning
confidence: 99%
See 1 more Smart Citation